Mencari Jati Diri di Dunia Digital: Analisis Identitas Gen Z Menurut Giddens - Al- Yahya, Qathrun Nada; Tjoetra, Afrizal (Master Program in Sociology, Faculty of Social and Political Sciences, Universitas Sriwijay, 2026)
This study discusses the development of digital technology that has changed social structures and the way individuals construct their identities, particularly among Generation Z. This study aims to understand how Generation Z constructs and negotiates identity in the digital age using Anthony Giddens' theory of reflexive modernity as a framework for analysis. This study uses a qualitative method with a descriptive approach through a literature review focusing on concepts related to reflexivity, modernity, and digital identity. The results show that Generation Z's identity is fluid and constantly changing, shaped through daily reflective practices in the virtual world such as sharing content, interacting online, and building a self-image (self-branding). The negotiation between self-authenticity and digital social demands is evident in how Generation Z presents itself and manages public perceptions of its existence. Social media functions not only as a means of expression but also as a space for reflecting on personal values and forming self-meaning. The conclusion shows that the digital identity of Generation Z is the result of a dynamic and responsive reflective process to technological changes and the modern social environment.